Supporting health science students' communication skills: Avoiding pitfalls. Issue 8 (March 2016) - Jain, Neera R.; Meeks, Lisa M.
Abstract : Communication is an area fraught with difficulty, particularly in the health science arena, where communication is central to patient safety and student progress. Indeed, the ability to communicate effectively is one of the mandatory curricular content areas for medical students as outlined by the Liaison Committee on Medical Education's 2016–17 accreditation standards, "7.8 Communication Skills: The faculty of a medical school ensure that the medical curriculum includes specific instruction in communication skills as they relate to communication with patients and their families, colleagues, and other health professionals."